MONITORING OF REGULAR AND SPORADIC IONOSPHERIC VARIATIONS ON THE SINGLE-HOP HF RADIO PATHS - Reznychenko, A. I.; Koloskov, A. V.; Yampolski, Y. M. (Видавничий дім «Академперіодика», 2018)
PACS numbers: 94.20.VvPurpose: Diagnostics of regular and sporadic ionospheric variations using coherent systematic monitoring of spectral characteristics of the probe HF signals on the inclined singlehop radio paths.Design/methodology/approach: Two HF receiving stations located at the Low Frequency Observatory of the Institute of Radio Astronomy, National Academy of Sciences of Ukraine, (Martove, Kharkiv region) and in Tromsø (Norway) were recording the signals at 9.996 MHz radiated by the radio station of the Exact Time and Frequency Service during the entire year of 2013. We estimated variations of the intensity and Doppler frequency shift (DFS) of the probe radiation derived from the power spectra recorded in the both observation points. The time series of these characteristics of the signals were compared with the independent estimates of the critical frequencies of the F2 ionospheric layer, as well as with indices of solar and magnetic activity. The correlation relationship between the time series were found.Findings: Systematic coherent measurements of spectral characteristics of the probe HF signals on two single-hop radio paths (high- and mid-latitude) have been made. The regular (background) variations of the diurnal dependences of intensities and DFS, caused by changes under the illumination conditions of the examined radio paths during the full annual cycle of observations, have been investigated. An empirical dependence between the moments of characteristic changes in DFS, “radio-sunrise” and “radio-sunset” with the solar terminator passage at various altitudes in the midlatitude and polar ionosphere was determined. Polar day conditions and growth of absorption in the midday and afternoon play the determining role for the high-latitude radio path in summer. An index characterizing the time interval when the signals propagate below the maximum usable frequency (the duration of the “radio-day”) is proposed. For the disturbed ionospheric conditions, the 27-day variations in the “radio-day” duration and the behavior of the critical frequencies of the F2 ionospheric layer are detected. The periodicity of these variations and their synchronism with the F10.7 index of solar activity can be explained by multiple influence on the ionosphere of a long-lived active region in the chromosphere during the rotation of the Sun around its own axis. The availability of using the data of HF monitoring for diagnostics of the sporadic ionospheric disturbances was demonstrated on the example of data analysis during a powerful X-ray flare on the Sun and subsequent magnetic storm.Conclusions: The developed methods of the analysis of the data of ionospheric sounding by non-specific HF signals can be used for diagnostics and identification of ionospheric disturbances.Key words: ionosphere, solar terminator, radio path, solar activity,magnetic stormManuscript submitted  25.09.2018Radio phys. radio astron. 2018, 23(4): 266–279REFERENCES1. BIBL, K. and REINISCH, B. W., 1978. The Universal Digital Ionosonde. Radio Sci. vol. 13, no. 3, pp. 519–530. DOI: https://doi.org/10.1029/rs013i003p005192. EVANS, J. V., 1969. Theory and practice of ionosphere study by Thomson scatter radar. Proc. IEEE. vol. 57, no. 4, pp. 496–530. DOI: https://doi.org/10.1109/PROC.1969.70053. KOLOSKOV, A. V., YAMPOLSKI, Y. M., ZALIZOVSKY, A. V., GALUSHKO, V. G., KASHCHEYEV, A. C., LA HOZ, C., BREKKE, A., BELYEY, V. S. and RIETVELD, M. T., 2014. Network of internet-controlled HF receivers for ionospheric researches. Radio Phys. Radio Astron. vol. 19, no. 4, pp. 324–335. (in Russian). DOI: https://doi.org/10.15407/rpra19.04.3244. ZALIZOVSKI, A. V., GALUSHKO, V. G., KASHCHEEV, A. S., KOLOSKOV, A. V., YAMPOLSKI, Y. M., EGOROV, I. B. and POPOV, A. V., 2007. Doppler Selection of HF Radiosignals on Long Paths. Geomagn. Aeron. vol. 47, no. 5, pp. 636–646. DOI: https://doi.org/10.1134/S001679320705012X5. ZALIZOVSKI, A. V., KASCHEEV, S. B., YAMPOLSKI, Y. M., GALUSHKO, V. G., BELEY, V. S., ISHAM, B., RIETVELD, M. T., LA HOZ, C., BREKKE, A., BLAGOVESHCHENSKAYA, N. F. and KORNIENKO, V. A., 2009. Self-scattering of a powerful HF radio wave on stimulated ionospheric turbulence. Radio Sci. vol. 44, no. 3, id. RS3010. DOI: https://doi.org/10.1029/2008RS0041116. NAJMI, A., MILIKH, G., YAMPOLSKI, Y. M., KOLOSKOV, A. V., SOPIN, A. A., ZALIZOVSKI, A. V., BERNHARDT, P., BRICZINSKI, S., SIEFRING, C., CHIANG, K., MORTON, Y., TAYLOR, S., MAHMOUDIAN, A., BRISTOW, W., RUOHONIEMI, M. and PAPADOPOULOS, K., 2015. Studies of the ionospheric turbulence excited by the fourth gyroharmonic at HAARP. J. Geophys. Res. Space Phys. vol. 120, no. 8, pp. 6646–6660. DOI: https://doi.org/10.1002/2015JA0213417. KASCHEEV, S. B., KOLOSKOV, A. V., ZALIZOVSKI, A. V., GALUSHKO, V. G., PIKULIK, I. I., YAMPOLSKI, Y. M., KURKIN, V. I., LITOVKIN, G. I., ORLOV, A. I. and PETKO, P. V., 2009. Experimental Investigation of Spectral Characteristics of HF Signals at Long and Ultra-Long-Range Radio Paths. Radio Phys. Radio Astron. [online]. vol. 14, no. 1, pp. 12–25. (in Russian). [viewed: 07.09.2018]. Available from: http://rpra-journal.org.ua/index.php/ra/article/view/5298. KASCHEEV, S. B., ZALIZOVSKI, A. V., KOLOSKOV, A. V., GALUSHKO, V. G., PIKULIK, I. I., YAMPOLSKI, Y. M., KURKIN, V. I., LITOVKIN, G. I. and ORLOV, A. I., 2009. Frequency Variations of HF Signals at Long-Range Radio Paths during a Solar Eclipse. Radio Phys. Radio Astron. [online]. vol. 4, no. 4, pp. 353–366 (in Russian). [viewed: 07.09.2018]. Available from:http://rpra-journal.org.ua/index.php/ra/article/view/5009. ZALIZOVSKI, A. V., KOLOSKOV, A. V. and YAMPOLSKI, Y. M., 2015.  Studying in Antarctica the time-frequency characteristics of HF signals at the long radio paths. Ukrainian Antarctic Journal [online]. no. 14, pp. 124–137.(in Russian). [viewed: 07.09.2018]. Available from: http://nbuv.gov.ua/UJRN/uazh_2015_14_1410. CHERENKOV, G. T., ed. 1979. Standard frequency and time signals. Characteristics and schedule of transmittings through radio stations, television and sound broadcast network. The Bulletin. Moscow, USSR: Standards Publishing House. (in Russian).11. WINRADIO by RADIXON, 2018. WR-G313i [online]. [viewed 07.09.2018]. Available from: https://www.winradio.com/home/g313i.htm12. GALUSHKO, V. G. and YAMPOLSKI, YU. M., 1996. Ionospheric diagnostics using wave field diffraction near the caustic. Radio Sci. vol. 31, no. 5, pp. 1109–1118. DOI: https://doi.org/10.1029/96RS0173713. DOLUKHANOV, M. P., 1972. Propagation of radio waves. Moscow, USSR: Svyaz Publ. (in Russian).14. TROMSØ GEOPHYSICAL OBSERVATORY, UIT, THE ARCTIC UNIVERSITY OF NORWAY, 2015. Archive ionograms Tromsø 2003 -> today [online]. [viewed: 07.09.2018]. Available from: http://geo.phys.uit.no/iono-data/ionosonde.html15. IZMIRAN, 2006. Moscow Digisonde DPS-4 #045 [online]. [viewed: 07.09.2018]. Available from: http://dps.izmiran.ru/16. IRA NASU, DEPARTMENT OF RADIOPHYSICS OF GEOSPACE, 2018. K-Indexes of geomagnetic activity [online]. [viewed: 07.09.2018]. Available from: http://geospace.com.ua/en/data/metmag_ki.php17. TROMSØ GEOPHYSICAL OBSERVATORY, UIT, THE ARCTIC UNIVERSITY OF NORWAY, 2018. Geomagnetic Data [online]. [viewed: 07.09.2018]. Available from: http://flux.phys.uit.no/geomag.html18. SPACE WEATHER PREDICTION CENTER, NATIONAL OCEANIC AND ATMOSPHERIC ADMINISTRATION, 2018. Data Service [online]. [viewed: 07.09.2018]. Available from: ftp://ftp.swpc.noaa.gov/pub/warehouse/2013/19. HUNSUCKER, R. D. and HARGREAVES, J. K., 2002. The High-Latitude Ionosphere and its Effects on Radio Propagation. Cambridge: Cambridge University Press. DOI: https://doi.org/10.1017/CBO978051153575820. GODDARD MEDIA STUDIOS, 2013. Solar Storm Near Earth Caused by March 15, 2013 Fast CME [online].[viewed: 07.09.2018]. Available from: https://svs.gsfc.nasa.gov/1122